Shear Bond Strengths of Methacrylate- and Silorane-based Composite Resins to Feldspathic Porcelain using Different Adhesive Systems - Narmin Mohammadi; Maryam Shakur Shahabi; Soodabeh Kimyai; Fatemeh Pournagi Azar; Mohammad Esmaeel Ebrahimi Chaharom (Tabriz University of Medical Sciences, 2015)
Background and aims. Use of porcelain as inlays, laminates and metal-ceramic and all-ceramic crowns is common in modern dentistry. The high cost of ceramic restorations, time limitations and difficulty of removing these restorations result in delays in replacing fractured restorations; therefore, their repair is indicated. The aim of the present study was to compare the shear bond strengths of two types of composite resins (methacrylate-based and silorane-based) to porcelain, using three adhesive types. Materials and methods. A total of 156 samples of feldspathic porcelain surfaces were prepared with air-abrasion and randomly divided into 6 groups (n=26). In groups 1‒3, Z250 composite resin was used to repair porcelain samples with Ad-per Single Bond 2 (ASB), Clearfil SE Bond (CSB) and Silorane Adhesive (SA) as the bonding systems, afterapplication of silane, respectively. In groups 4‒6, the same adhesives were used in the same manner with Filtek Silorane composite resin. Finally, the shear bond strengths of the samples were measured. Two-way ANOVA and post hoc Tukey tests were used to compare bond strengths between the groups with different adhesives at P<0.05. Results. There were significant differences in the mean bond strength values in terms of the adhesive type (P<0.001). In addition, the interactive effect of the adhesive type and composite resin type had no significant effect on bond strength (P=0.602). Conclusion. The results of the present study showed the highest repair bond strength values to porcelain with both com-posite resin types with the application of SA and ASB.